Happy Hunting Ground - Payne, Leonidas Warren, 1873-1945.; Dobie, J. Frank (James Frank), 1888-1964.; Project Muse. (University of North Texas Press, 2000)
Annotation This is a miscellany of Texas and Southwestern folklore collected and written by ten folklorists in 1925. Included are articles on Mexican popular ballad; Spanish songs of New Mexico; versos of the Texas vaqueros; reptile myths; the cowboy dance of the northwest; superstitions of the Northern Seas; oil field diction; folk tales of the Chibcha nation; the human hand in primitive art; Indian pictographs near Lange's Mill. Includes "When the Woods Were Burnt," by L.W. Payne, Jr., the first pamphlet of the Texas Folklore Society. Book jacket.
Reprint of the 1964 facsimile ed., published by Southern Methodist University Press.
Description based on print version record.
Keywords: Folklore; Folklore -- Texas; Folklore; Texas; Electronic books